Preparation and infrared to visible upconversion luminescence of Yb2O3:Ho3+ nanocrystalline powders. Issue 5 (1st April 2017) - Guo, Weihua; Hao, Hongshun; Jin, Shanshan; Su, Qing; Li, Hong; Hu, Xiaofei; Gan, YiJie; Qin, Lei; Gao, Wenyuan; Liu, Guishan
Abstract: Yb2 O3 :Ho 3+ nanocrystalline powders were synthesized through a solid state reaction method. X-ray diffraction analysis and field emission scanning electron microscopy were used to analyze the phase composition and morphology of the powders. Then under the 980 nm excitation of laser diode, the fluorescence of the crystals was studied via a fluorescence spectrometer. The green and red emissions centered on 551 and 668 nm were observed, and the green band dominated the emission spectrum. The effect of the concentration of Ho 3+ on the upconversion luminescence intensity was discussed and the possible upconversion emission mechanism was explained. It indicates that like other metal oxide nanoparticles, Yb2 O3 could also be a potential host material for doping to prepare the upconversion phosphor.